2017
DOI: 10.1515/spma-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

A shorter proof of the distance energy of complete multipartite graphs

Abstract: Caporossi, Chasser and Furtula in [Les Cahiers du GERAD (2009) G-2009 conjectured that the distance energy of a complete multipartite graph of order n with r ≥ parts, each of size at least 2, is equal to (n − r). Stevanovic, Milosevic, Hic and Pokorny in [MATCH Commun. Math. Comput. Chem. 70 (2013), no. 1, 157-162.] proved the conjecture, and then Zhang in [Linear Algebra Appl. 450 (2014), 108-120.] gave another proof. We give a shorter proof of this conjecture using the interlacing inequalities of a positve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…us, we are interested in finding the distance energy of some special graphs. For example, it has been proved in [6][7][8] that…”
Section: Introductionmentioning
confidence: 99%
“…us, we are interested in finding the distance energy of some special graphs. For example, it has been proved in [6][7][8] that…”
Section: Introductionmentioning
confidence: 99%
“…(1), was recently introduced [7]. This definition was motivated by the much older [8] and nowadays extensively studied [9,10,11,12] graph distance energy. In [13], Estrada introduced another graph-spectrum-based invariant of graphs, which was later called the Estrada index, defined as…”
Section: Introductionmentioning
confidence: 99%
“…In [9], the distance energy of a graph is defined as the sum of the absolute values of the distance eigenvalues. Subsequently, many interesting results were obtained related to distance energy (for example see [1, section 8]) and in particular in [19,21], authors computed the distance energy of complete t-partite graph and moreover, in [21], it was also shown that for fixed value of n and t, the distance energy of complete t-partite graphs on n vertices is maximal for complete split graph S n,t and is minimal for Turán graph T n,t . Later in [12], majorization techniques were used to prove that S n,t and T n,t are also the extremal graphs for which the distance spectral radius of complete t-partite graphs on n vertices that attains its maxima and minima, respectively.…”
Section: Introductionmentioning
confidence: 99%